Internationalization of SMEs: Relevance of the Theories and Antecedents - Lakshman, Duleepa; Kumarasinghe, J.; Weerasinghe, R. (Asian Journal of Economics, Business and Accounting, 2023)
Scholars have paid close attention to developing several theories and models for the internationalization of small and medium-sized enterprises. These theories and models explain the firm strategic directions and gradual process of international expansion. This theoretical literature review aims to comprehensively examine the wide array of literature relating to theories and models of SME internationalization and the antecedents of internationalization. This study looks at the connections and contrasts between various internationalization theories and models, discusses their shortcomings, and provides theory-based insights to SMEs in understanding the internationalization process. Further, this paper examines the different antecedents of SME internationalization and prior empirical validations of those antecedents. According to the literature analysis, it has been identified that most SME internationalization studies are done in developed countries. Moreover, most of the internationalization theories and models are built in developed countries by observing the behavior of large firms. Hence, most of these theories and models may be insufficient to explain SME success in developing and emerging markets. Further, companies currently use more strategic approaches (such as joint ventures, and strategic alliances) to internationalize their operations. As a result, it is argued that the existing internationalization literature and theories are insufficient to explain the internationalization of SMEs in developing countries in the modern world.
Keywords: Small and medium enterprises; Internationalization; Resources